“Exploring the efficacy and mechanistic action of traditional Chinese medicine-derived phytochemicals in rheumatoid arthritis” - Uma Palanikumar; Rajagopal Balasubramanian; Prasanna Seenivasan; Vellaikumar Sampathrajan; Thangavelu AU (Pharmacological Research - Modern Chinese Medicine)
Introduction: Rheumatoid arthritis [RA] is an autoimmune chronic inflammatory condition that leads to joint degeneration and functional disability. The most advanced pharmacological therapies that have been available for a long time remain limited, as they are associated with adverse effects and incomplete disease remission. In contrast, Traditional Chinese Medicine [TCM] is a promising alternative, as it utilizes phytochemicals obtained from medicinal plants. Methods: This study explores the efficacy and mechanistic action of TCM-derived phytochemicals in the management of RA, with insights on in silico approaches, including molecular docking, ADME [Absorption, Distribution, Metabolism, and Excretion] studies, and network-based analysis using Cytoscape. We evaluated the interactions of flavonoids, alkaloids, terpenoids, and glycoside phytochemicals from key TCM plants with critical targets in RA, like pro-inflammatory cytokines [TNF-α, IL-1β], enzymes [COX-2, MMP-9], and signaling pathways [NF-κB, JAK/STAT], considering the applications of computational tools. Results: The available evidence indicates that TCM phytochemicals modulate inflammation, inhibit key enzymes, and enhance anti-inflammatory responses for multi-target therapy of RA. In silico evidence of the efficacy and mechanistic actions is supportive of the promising therapeutic potential of TCM phytochemicals. Discussion: Despite their numerous therapeutic advantages, phytochemicals also present certain limitations, such as poor oral bioavailability, off-target interactions, and manufacturing challenges. These factors necessitate significant structural modifications before their potential use as drugs. In addition, this study underscores the importance of further experimental and clinical validation.